Water contact angle is not a good predictor of biological responses to materials - Alexander, Morgan R.; Williams, Paul (AIP Publishing, 2017)
Often the view is expressed that water contact angle (WCA) or other wettability/surface energy measurements made on a material surface can be used to predict cellular attachment to materials, e.g., bacteria attach to hydrophobic surfaces. In this article, the authors present a perspective emerging from their work that has failed to find relationships between WCA and microbial and stem cell attachment within large diversity material libraries and compare with the literature concluding that such simple rules are (unfortunately) wholly inadequate to explain cell–material interactions.